Relationships Between Neurofibromatosis-2, Progesterone Receptor Expression, the Use of Exogenous Progesterone, and Risk of Orbitocranial Meningioma in Females - Supartoto, Agus; Sasongko, Muhammad Bayu; Respatika, Datu; Mahayana, Indra Tri; Pawiroranu, Suhardjo; Kusnanto, Hari; Sakti, Dhimas Hari; Nurlaila, Prima Sugesty; Heriyanto, Didik Setyo; Haryana, Sofia Mubarika (Frontiers in Oncology, 2019)
Background: The pathogenesis of meningioma in females and its association with exogenous progesterone is remained unclear. This study was aimed to examine expression of Progesterone receptor (PR) and Neurofibromatosis-2 (NF2) and assess their relationships to history of exogenous progesterone use and risk of meningioma. Methods: Our study was a case-control study that involves 115 females, 40 cases who diagnosed with orbito-cranial meningioma and 75 controls of healthy, that has been presented in previous study. The demographic characteristics, reproductive factors, and history of progesterone use were obtained in−depth face-to-face interviews. PR and NF2 mRNA were assessed by real-time quantitative polymerase chain reaction (RT-qPCR) on serum specimens. Results: The mean age of participants in cases vs. controls were 46.6±6.2 vs. 46.5±7.45 (P=0.969). The expression of PR and NF2 in cases was significantly lower than in controls. The longer duration of progesterone exposure was significantly associated with lower expression of PR and NF2. Significant association between lower expression of PR (OR 11.7; 95% CI 4.17 – 32.9; P<0.001 comparing the lowest quartile vs. 3 highest quartile of PR) and NF2 (OR 4.23; 95% CI 1.85 – 9.67; P=0.001 comparing the 2 lowest quartiles vs. 2 highest quartiles) with increased risk of meningioma were also reported. Conclusion: In this study we showed that the longer the exposure to exogenous progesterone, the lower the expression of PR and NF2 mRNA in the serum. Low expression of PR and NF2 were associated with higher risk of meningioma, suggesting that low PR expression and inactivation of NF2 might play a key role in progesterone-associated meningioma tumorigenesis and may be potential clinical marker for females at higher risk of meningioma.